On the trade-off between privacy and utility in mobile services: a qualitative study - Liu, Y; Simpson, A (Springer Verlag, 2020)
While the widespread use of mobile services offers a variety of benefits to mobile users, it also raises serious privacy concerns. We report the results of a user study that investigated the factors that influence the decision-making process pertaining to the trade-off between privacy and utility in mobile services. Through two focus groups, 16 individual interviews and a questionnaire survey involving 60 participants, the study identified awareness and knowledge of privacy risks, trust in service providers, desire for mobile services, and belief of cyber privacy as four factors that contribute to the perceived trade-off. The results also suggest that, with appropriate adoption, privacy-preserving tools can positively influence the privacy trade-off. In addition, our findings explore the cultural differences regarding privacy between participants from western countries (with the UK as the main representative) and China. In particular, the results suggest that participants from China are more likely to be comfortable with a government department protecting their individual privacy, while participants from western countries are more likely to wish to see such responsibility reside with some combination of individuals and non-governmental organisations.